The Intelligent Leader : unlocking the 7 secrets to leading others and leaving your legacy - Mattone, John, author (Hoboken, New Jersey: John Wiley & Sons, 2020)
The Intelligent Leadership Code articulates Mattone's approach. Starting with an in-depth argument for why developing the inner core is so crucial to unlocking a leader's "outer" capacities, he lays out the path and practice of becoming an intelligent leader through his Seven Pillars: * The First Pillar - Thinking Differently, Thinking Big * The Second Pillar - The Vulnerability Decision * The Third Pillar - Having a Mindset of Privilege vs. a Mindset of Duty * The Fourth Pillar - Leveraging Your Gifts and Addressing Your Gaps * The Fifth Pillar - Having the Courage to Execute with Pride, Passion and Precision * The Sixth Pillar - Staying Present and Being Vigilant * The Seventh Pillar - Course Correction Each chapter focuses on a different pillar and are accompanied by a series of valuable tools and assessments that help readers put the insights directly into practice, including the Mattone Leadership Enneagram Inventory ($110 value), available for free online and through the book's complementary app. Readers who take the MLEI will be given a personalized report and then have the option, for purchase, of scheduling a consultation with an IL coach or Mattone himself to develop a strategy for growth" Provided by publisher.
Keywords: Leadership; Executive Ability